Metabolic targets and physical activity in breast cancer - Guinan, Emer (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Physiotherapy, 2013)
Breast cancer is the most common female cancer diagnosed in Ireland and worldwide. Breast cancer risk and outcome may be managed through modifiable risk factors including body weight and physical activity. Physical activity is hypothesised to protect against breast cancer occurrence and recurrence through alterations in several obesity-related metabolic pathways. The aim of this thesis was to examine the presentation of and relationships between metabolic dysfunction and habitual physical activity in two high risk groups; breast cancer survivors and unaffected carriers of mutations in the BRCA genes. Study I and II involve breast cancer survivor cohorts while in Study III unaffected BRCA mutation carriers are examined.
Keywords: Physiotherapy, Ph.D.; Ph.D. Trinity College Dublin